PENGARUH SISTEM IMFORMASI MANAJEMEN DAN ANALISIS KEBIJAKAN SEKOLAH TERHADAP MUTU LAYANAN TENAGA ADMINISTRASI DI SEKOLAH MENENGAH ATAS NEGERI KOTA JAMBI - Zilawati, Zilawati; Fitri Nasution; Nur’aini, Nur’aini; Amiruddin, Amiruddin (Bajang Institute, 2024)
Along with the development of science, information and communication technology, scientific progress has been made in various fields, including education. Education is a strategic alternative in educating the nation and the main capital for developing a nation. Ideally, education must be oriented towards improving the quality of services in order to create an educational process that can encourage students to be enthusiastic about learning which in the end is expected to produce quality educational output. Education problems in Indonesia, especially regarding the quality of educational administration services, are often felt by users of educational services. Complicated service processes, less effective administration procedures and lengthy bureaucratic processes that must be followed often make students and parents complain about the situation. This is usually caused by several factors such as: limited use of educational Management Information Systems, weak data processing, and weak quality of service provided by administrators who are less alert and do not prioritize service towards the satisfaction of educational service users. The method used in this research is the causal survey method. According to Umar, a causal survey is a method of analyzing the relationships between one variable and other variables. The type of research used by the author is non-experimental research (survey research) with a quantitative approach, namely research on data collected and expressed in the form of numbers. There is a positive and significant influence of the management information system and school policy analysis on the service quality of the administrative staff of the Leading State Senior High School in Jambi City.